Tradisi Adat Jawa Tujuh Bulan pada Ibu Hamil (Tingkeban) Desa Citaman Jernih Susun VII Jln. Garuda Perbaungan Kabupaten Serdang Bedagai - Dewi Robiyanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This writing is motivated by the community tradition of the Seven Months Ceremony by the Javanese tribe regarding Tingkeban.(Tingkeban) pregnant women from the people of Citaman Clear Village, DSN VII, Perbaungan District, Serdang Bedagai Regency. The aims of this research are: 1) To find out the meaning of the Tingkeban Ceremony for the Community of Citaman Clear Village and VII, Perbaungan District, Perbaungan City; 2) To find out what educational values are contained in the implementation of the Tingkeban Ceremony in Citaman Clear Village and VII, Perbaungan District, Serdang Bedagai Regency. This writing uses qualitative methods with data collection techniques using interviews, observation and documentation. The results of this community service show that the Seven Months Ceremony (Tingkeban) is a ceremony carried out at the 7th month of pregnancy. The tradition of the Seven Monthly Ceremony (Tingkeban) for pregnant women contains educational values in the lives of the people of Citaman Jenih DSN VII Village, Perbaungan District, Serdang Bedagai Regency. Understanding the Seven Months Tradition The seven months tradition is a ritual or practice carried out by a pregnant woman during the seven months of pregnancy. It includes various actions and deeds that are considered to help the well-being of the mother and baby during pregnancy. Origins of Traditions These traditions originate from various cultures and religions around the world, with the aim of providing emotional, physical and spiritual support to pregnant women. Some practices may have more distant historical roots. Practices in the Seven Months Tradition Practices vary, but can include prayer, religious rituals, use of herbal concoctions or traditional medicines, changes in diet or lifestyle, and emotional counseling. Benefits During Pregnancy Some people believe that the seven months tradition helps prepare the mother’s body for childbirth, reduces the risk of pregnancy complications, and provides emotional and spiritual support during pregnancy. The Importance of Medical Counseling Although this tradition can provide additional support, it is important to still consult with a medical professional to ensure the mother’s health. And the baby during pregnancy. Cultural and Religious Variations Practices in seven monthly traditions can vary significantly between cultures and religions. The Importance of Balance It is important to maintain a balance between these traditions and modern medical knowledge during pregnancy in order to get the best outcomes for the health of mother and baby.